A longitudinal study on the effect of aerobic exercise intervention on the inhibitory control in college students with internet addiction - Wang, Yi; Li, Xiangkun (Frontiers in Human Neuroscience, 2025)
ObjectivesThis study aimed to investigate the effects of aerobic exercise on reactive inhibitory control in college students with internet addiction, examining both behavioral and electrophysiological changes over time.MethodsA longitudinal study design was adopted, involving 48 male college students with internet addiction who were randomly assigned to either a control group or an experimental group. Participants in the experimental group engaged in 40 min aerobic cycling sessions three times per week for 12 weeks, while the control group maintained their usual physical activity levels without any intervention. A 3 × 2 × 3 mixed-factorial design was utilized, incorporating three time points (pre-experiment, 6 and 12 weeks), two groups (control and experimental), and three electrode sites (Fz, F3, F4). This design enabled the examination of the effects of aerobic exercise on reactive inhibitory control and its temporal dynamics in college students with internet addiction.ResultsA significant main effect of group was observed. Specifically, the experimental group demonstrated a significantly higher Nogo accuracy rate compared to the control group at both the mid-test (P < 0.01) and post-test (P < 0.001). Within the experimental group, the Nogo accuracy rate at the mid-test and post-test was significantly higher than at the pre-test (P < 0.001), with the post-test accuracy rate also significantly higher than the mid-test (P < 0.05). Time-frequency analysis revealed that, under the Nogo task, the energy values in the beta frequency band during the early (100–500 ms) and late (600–750 ms) time windows were significantly higher at the mid-test and post-test compared to the pre-test (P < 0.05), with the post-test values significantly exceeding those at the mid-test (P < 0.05).Conclusion(1) Moderate-intensity aerobic exercise significantly improves reactive inhibitory control in college students with internet addiction, with the magnitude of improvement increasing over the duration of the intervention. (2) Increased beta band energy during the early (100–500 ms) and late (600–750 ms) time windows serve as a key neurophysiological indicator of this enhancement.